Edukasi interaktif kesehatan anak melalui kegiatan English Camps di Kampung Pandai Inspiratif, Palembang - Najmah, Najmah; Vanvie, Chynta Rahma; Jordanti, Happy Mira; Rahmawati, Mala; Sucirahayu, Citra Afny; Savira, Mahwa; Ariqa, Nur Zihan; Irwantika, Nanda; Trisnaini, Inoy (Fakultas Kedokteran Universitas Sriwijaya, 2022)
At elementary school, children will start learning by introducing personality values ​​such as positive habits that can be applied and taught at school. The rise of sexual cases in children in educational institutions and in the surrounding environment is something that needs attention. In addition to other problems that are often faced by elementary school-agee children (SD) such as those related to clean and healthy living behavior (PHBS), ranging from maintaining personal hygiene and maintaining the cleanliness of the surrounding environment that has not been implemented properly, causing various health problems. Children often become victims of disasters that occur due to not being able to save themselves, due to the lack of understanding the disaster, one of the common disasters that occur in Palembang City is fire. Inspirational Smart Village is a program to educate children about messages on balanced nutrition, personal hygiene, reproductive health, environmental health and understanding fire response actions. After evaluating the results of the activity by conducting a post test to test the knowledge related to the education that has been given. The results of the post test were analyzed using a data processing application to see the average value of children's knowledge. The design in this study is descriptive analytic with a cross sectional study approach with a sample of 60 respondents. The cut-off point value is taken from the median value of 80.00. The results obtained were 42 children with good knowledge (63.6%), and 24 people with less knowledge (36.4%). Children's knowledge can be increased after educational efforts are made on messages about balanced nutrition, personal hygiene, reproductive health, environmental health and disaster response.